PENGARUH SENAM OTAK TERHADAP PENURUNAN TINGKAT KECEMASAN PESERTA UJI KOMPETENSI KEAHLIAN PERDAGANGAN IMPOR PADA LEMBAGA PELATIHAN ASI TRAINING CENTRE KOTA BEKASI JAWA BARAT - Ali, Mohammad; Aminoto, Toto (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2024)
An importer must have expertise in this field. One thing that shows is having a certificate of expertise in the field of import trade. To get it, participants must pass certification. Because of these demands, many participants experienced mental disorders, namely anxiety. Anxiety levels often arise due to psychological pressure. In this case, participants are required to pass a skills test in the field of import trade. To reduce anxiety levels, one form of exercise is brain exercise. This research aims to prove the influence of brain exercise on reducing the anxiety level of training participants at the ASI Training Center Institute in Bekasi City. The benefit of this research for physiotherapy is that it adds to the literature to prove that brain exercise can reduce the anxiety level of training participants. The sampling technique used was purposive sampling. This group was divided into two research groups. Treatment group with intervention and control group without intervention. Each group consisted of 15 respondents. Statistical analysis used the independent t test. The research results showed that there were differences between the control group and the treatment group. These results indicate that the value of the treatment group is lower than that of the control group. Thus, it can be concluded that the treatment group was more effective than the control group. So it was concluded that brain exercise had an effect on reducing anxiety levels.Key words: Keywords: Jenga game, Anxiety, saturation, Psychology